If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = h * h Multiply h * h y = h2 Solving y = h2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = h2
| =(x-1)(x^2+5x-6) | | -7x-6=2+3x | | y=6h*h | | x^4-52500x^2+1250000=0 | | -(3x+9)=24 | | 12.36=S-6.63 | | 3x-12(3x)=0.25 | | 10x+3y+5=0 | | 6y+3=-y+31 | | 2.5n=18.5 | | 2g-3.1=1.7 | | -5x-7=6x+5(4-8x) | | 6y-2x+1= | | -18m-24=-6+48 | | 11-3x=-4x | | 7x+3=4x+3 | | 4d+9=7d | | 5b+7-12b-29= | | 4n+1=5n+20 | | 14n-6-5n-29= | | 3[x-4]=8[x-9] | | 10x+3x+8x= | | 5times=135 | | (x-1)(x^2+5x-6)= | | (6x+6)+(10x-30)= | | 2x^2-6x=80 | | 7-(4n-8)=7-5n | | 5[x-4]=2[x-7] | | 9x+4+3+8=12 | | 7x^2+76x=8 | | 18c-4-2c+12= | | 54=x+5x |